Icon Size Effect on Selection Speed and Accuracy - Satcharoen, Kleddao (My University, 2020)
The objective of this research is to evaluate the effect of icon size on selection speed and accuracy. An experiment was designed for investigation of icon selection on a mobile device. A set of 20 icons, with a combination of six icon sizes (16pix to 96pix square), was used to generate 120 trials per subject (n = 52). Selection time (seconds) and accuracy (accurate/inaccurate) were collected. Data was analyzed using chi-square tests. Analysis of TimeｘAccuracy showed that 2s had the lowest inaccuracy rates (.84%), while 5s+ had the highest inaccuracy rates (8.86%). When considering Icon SizeｘTime→Accuracy showed that there were significant differences for most groups. The highest inaccuracy rates were seen for small icons (48pix and smaller), and inaccuracy climbed at higher Time. The implication of this study is that icon size can negatively influence selection speed and that higher selection speed was associated with lower accuracy as well.
Keywords: accuracy; icon selection; Icon size; response time